Tourism Small And Medium Enterprise Competitiveness : The Influence Of Entrepreneurial Attitudes Towards Business Performance - Ho, Koon Song (UTeM, 2018)
The data have shown that is over demand and high competition among the SME hotel. Following the knowledge-based view approach, this contribution aims to study how the entrepreneur attitude influence tourism SME entrepreneur toward their business performance. Besides that, the number of foreign visitor travel to Malaysia was increase from year 2008-2018. That why as the SME entrepreneur personality attitude play the important role to manage their business and adapt in the competitive market. The hypotheses proposed in our research framework are survey by questionnaires to 150 SME hospitality entrepreneurs. The entrepreneurial attitudes which are personal control, self-esteem and innovation will determine whether will have significant and positive relationships with business performance. It also will find out which are the most influences attitudes towards the business performance. The finding may help SME entrepreneur self-improvement and enhance their competitive advantage to their business.